2016
DOI: 10.4038/cmj.v60i4.8224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in benign gastric ulcers in a cohort of Sri Lankan patients

Abstract: Helicobacter pylori prevalence is decreasing globally and prevalence of non H. pylori gastric ulcers is increasing. The following study was conducted to assess the prevalence of H. pylori in benign gastric ulcers in a sample of Sri Lankan patients. This was a cross-sectional study of 59 dyspeptic patients with benign gastric ulcers. Multiple endoscopic gastric biopsies were obtained and histology, immunohistochemistry and polymerase chain reaction were performed for H. pylori detection. An immunochromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…H. pylori gastric colonization is acquired early in life (almost always before the age of 10 years), and, in the absence of antibiotic therapy, generally persists for life[12,22,23]. The prevalence of H. pylori ranges from 35% to 90% in different populations[21,24-28]. It presents in 70%-90% of the population in developing countries and 35%-40% in developed ones[21,29].…”
Section: H Pylori Is One Of the Etiological Factors Of Pudmentioning
confidence: 99%
“…H. pylori gastric colonization is acquired early in life (almost always before the age of 10 years), and, in the absence of antibiotic therapy, generally persists for life[12,22,23]. The prevalence of H. pylori ranges from 35% to 90% in different populations[21,24-28]. It presents in 70%-90% of the population in developing countries and 35%-40% in developed ones[21,29].…”
Section: H Pylori Is One Of the Etiological Factors Of Pudmentioning
confidence: 99%
“…The role of TNF‐α polymorphisms in severity of H. pylori‐ associated disease has not been studied in Sri Lanka. Previous histological studies done in Sri Lanka have suggested that most H. pylori‐ infected patients have mild chronic gastritis and that development of gastric atrophy is not a significant problem. Multiple factors can contribute to a shift from mild to atrophic gastritis; however, host genetic factors can play a major role.…”
mentioning
confidence: 98%